Sex differences in genetic susceptibility of hippocampal subfields: A polygenic association study. (December 2021) - Genius, Patricia; Arenaza‐Urquijo, Eider M.; Operto, Greg; Evans, Tavia E.; Brugulat‐Serrat, Anna; Falcon, Carles; Minguillón, Carolina; Fauria, Karine; Adams, Hieab H.H.; de Moura, Manuel Castro; Piñeyro, David; Esteller, Manel; et al.
Abstract: Background: The hippocampus is involved in several complex diseases which display sex differences in their prevalence. Therefore, it can be hypothesized that sex‐specific genetic vulnerability in hippocampal formation might partially explain these differences. The aim of this study was to investigate whether the genetic predisposition to several complex diseases showed sex‐specific associations with the volumes of hippocampal subfields. Method: A total of 1, 071 cognitively unimpaired participants (45‐74 years) at increased risk for Alzheimer's disease (AD) (ALFA study), with available genotyping and neuroimaging data were included (62.6% women). Genetic predisposition was calculated through polygenic risk scores (PRSs) computed using the PRSice tool (v.1.25). A total of 33 PRSs were estimated from the most recent genome‐wide association meta‐analyses for several neurodegenerative, vascular and metabolic diseases, as well as for biomarkers of AD. Association analyses included the volumes of the hippocampal subfields quantified through high‐resolution 3D‐T1‐weighted magnetic resonance imaging scans and determined using Freesurfer (v.6.0). Sex‐stratified association analyses were estimated using linear regression models adjusted for age, education, and total intracranial volume. The threshold of significance was established by approximating the total number of effective tests. The resulting adjusted significance threshold was set at p <0.005. Result: PRSs were equally distributed among women and men, sharing a common pattern of variability [Figure 1]. Both groups showed increased genetic susceptibility for abnormal levels of AD biomarkers and for vascular, brain, as well as sleep disorders. Association analyses showed significant sex differences associated to several hippocampal subfields [Figure 2]. Specifically, in women, increased genetic risk of multiple sclerosis and neurodegenerative diseases was associated with larger cornu ammonis 1 (CA1), hippocampal tail and molecular layer, as well as with increased volume of the whole hippocampus. In men, a raised genetic risk of cerebral infarction, epilepsy and both short and long duration of habitual sleep was associated with reduced volumes of CA1, molecular layer, subiculum, and dentate gyrus. Conclusion: We provide evidence that genetic susceptibility differentially influences on hippocampal subfield volumes according to sex. This may explain sex‐specific patterns of neurodegeneration and biological vulnerabilities.